2022
DOI: 10.3390/su14137630
|View full text |Cite
|
Sign up to set email alerts
|

A New Framework for Sustainable Resilient Houses on the Coastal Areas of Khanh Hoa, Vietnam

Abstract: With the impacts of tropical storms on Vietnam’s residences, the aim of the study is to produce a new framework for designing sustainable resilient houses in Vietnam’s coastal areas. This study was based on the community’s need to develop a set of guidelines for improving the stability of domestic buildings in storm-prone areas. It also addresses some unresolved issues including storm-proofing techniques and sustainable development in coastal dwellings. The main findings of this study were defined by the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Numerous researchers have explored sustainable and cyclone-resilient housing solutions, offering guidelines for reducing storm impacts on buildings (resilient design) and minimizing environmental effects of reconstructions (sustainability) [60][61][62][63]. These guidelines address critical factors such as the shape of buildings or house plans, roof design, building height, building structure, energy efficiency, and resource utilization [64].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have explored sustainable and cyclone-resilient housing solutions, offering guidelines for reducing storm impacts on buildings (resilient design) and minimizing environmental effects of reconstructions (sustainability) [60][61][62][63]. These guidelines address critical factors such as the shape of buildings or house plans, roof design, building height, building structure, energy efficiency, and resource utilization [64].…”
Section: Discussionmentioning
confidence: 99%
“…Appendix A Figure A1. Clusters (specifically Vulnerability [39,46,50,[52][53][54][55][56][57][58][59]69,79,80] and Flexibility [43,44,49,56,[59][60][61][62][63][64][65][66]68,74,81]) from the selected records resulted from the literature review and selected records (keywords found in the records belonging to each thematic category in yellow stickers, research articles in light blue ones, review articles in blue ones, and conference papers in black ones). [41,48,75,77,80,82] resulted from the literature review and selected records (keywords found in the records belonging to each thematic category in yellow stickers, research articles in light blue ones, review articles in blue ones, and conference papers in black ones).…”
Section: Appendix Amentioning
confidence: 99%
“…However, the impact of globalization has been more pronounced in developed economies than in emerging ones, and has been susceptible to economic crises and protectionist policies. [2].…”
Section: Introductionmentioning
confidence: 99%